The Role of Scafolding Strategy as an Alternative to Improve Students’ Matematical Thinking Skills at SD Negeri 3 Kalipelus - Listiani Dwi Noviyanti; Ristiana Dyah Purwandari (Proceedings Series on Social Sciences & Humanities, 2025)
Mathematics is a universal science that has a major role in the development of knowledge, technology, and information (Sutarsa, 2021). It serves as the foundation for various disciplines, as every field of science inherently involves mathematics. Therefore, mathematics is taught at every level of education in Indonesia, from elementary schools to universities, to foster and develop students’ abilities in logical, analytical, systematic, critical, and creative thinking, as well as their collaboration skills. One of the mathematical competencies expected to be developed in schools is students’ mathematical thinking ability. This includes critical thinking, problem-solving, mathematical connections, mathematical reasoning, and creative thinking skills (Silviana, 2021). Background from this watchfulness because the ability of Class V students at SD Negeri 3 Kalipelus to solve mathematics problems remains relatively low, Students’ critical thinking skills are underdeveloped, as teachers tend to pay limited attention to how students respond to the problems, Students’ lack of active involvement often leads to their exclusion, which hinders the development of their mathematical critical thinking skills, Students still experience difficulties in identifying the relevant concepts, especially when the given problems involve more than one concept. Therefore, one of the alternative instructional strategies that teachers can apply to support students in the learning process is the scaffolding strategy. Scaffolding is a strategy that serves to bridge the gap between students’ existing knowledge and the new knowledge they are expected to acquire. Scaffolding is considered an effective and appropriate strategy for teachers to use when assisting students in solving mathematical problems. This is supported by research conducted by Yuntawati, titled “The Effectiveness of Scaffolding on Improving Mathematical Problem-Solving Ability.” The study yielded positive results, showing a significant difference in problem-solving abilities between the class that received scaffolding and the class that did not, indicating that scaffolding was effective in enhancing students’ mathematical problem-solving skills in that study.